Wooden sculpture in Romanesque Iberian Peninsula: a wide and attractive panorama. Lines of research - Jordi Camps i Sòria (Medievalista)
Romanesque polychromed wooden imagery in the Iberian Peninsula (12th-13th centuries) stands both as a valuable and complex heritage. Apart from some general lines that determine compositional and symbolic features, the local context, the liturgy, the artists or workshops and the influence of some prestigious models have created a highly attractive scenario. It is important to note that some statues that are preserved separately today may well be, from a broader perspective, part of larger ensembles of liturgical furniture. At the same time, the number of studies on technical and material aspects involving interdisciplinary work has increased. One of the questions that concern scholars the most is the spread of typology and stylistic trends. The influence of metal and precious metal works on tempered polychromed must be assessed. Other times, the spread of modalities confined to an area might well obey cult and pilgrimage reasons. Not all works, however, strictly follow one modality or another. Another hypothesis deals with the importation of some objects.